Unstandardizing Testing: Low-Scoring American Minority Students in the Crosshairs of Conservative Policymakers - Nighaoui, Sami Chedhli (Journal of Education in Black Sea Region, 2018)
That standardized tests do not accurately assess the true competencies of minority test takers is a widely shared claim among conservative educationists. The opt-out-of-testing community has lately grown unprecedentedly vocal in several states, questioning even more seriously the accountability of the testing system altogether. This paper adopts a Critical Race Theory perspective to investigate the conceptual underpinnings of conservative criticism as well as the interpretations made popular using quantitative methodology. The key premise of this paper is that a colorblind approach to testing understates the importance of a range of unquantifiable variables, mainly the linguitic and cultural backgrounds of the test takers, in determining assessment outcome. It attempts to demonstrate where specifically standardized tests may not be used as a reliable feedback mechanism and suggests that a more flexible assessment paradigm be considered, one that engages learning quality followup to keep cultural bias to a strict minimum.